2024
DOI: 10.3390/app14020499
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Evolution Network Model of the Landslide Disaster Chain: A Case Study of the Baige Landslide

Feng Gao,
Xiu Gao,
Chun Yang
et al.

Abstract: In the context of Western China’s unique geography, recurrent landslide disasters pose substantial threats to both resident safety and economic stability. The escalating frequency of these incidents emphasizes the critical need for innovative disaster research, particularly focused on the concept of a disaster chain. This research aims to enhance disaster preparedness and management strategies with the ultimate goal of minimizing losses. On the basis of predecessors, this study changes the previous analysis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The authors of [15,16] demonstrated that continuously monitoring soil moisture can significantly improve the accuracy of landslide risk assessment and the lead time for early warnings. In this study, we mainly focused on the in-depth monitoring of soil moisture through six indicators: soil bulk density, the angle of internal soil friction, soil shear strength, soil moisture content, the porosity ratio, and the Topographic Wetness Index.…”
Section: Basis and Selection Of Evaluation Indicatorsmentioning
confidence: 99%
“…The authors of [15,16] demonstrated that continuously monitoring soil moisture can significantly improve the accuracy of landslide risk assessment and the lead time for early warnings. In this study, we mainly focused on the in-depth monitoring of soil moisture through six indicators: soil bulk density, the angle of internal soil friction, soil shear strength, soil moisture content, the porosity ratio, and the Topographic Wetness Index.…”
Section: Basis and Selection Of Evaluation Indicatorsmentioning
confidence: 99%